Evidence that informs feeding practices in very low birthweight and very preterm infants in sub-Saharan Africa: an overview of systematic reviews. Issue 1 (11th August 2020) - Akindolire, Abimbola; Talbert, Alison; Sinha, Ian; Embleton, Nicholas; Allen, Stephen
Abstract : Background: Optimal feeding of very low birthweight (VLBW <1500 g)/very preterm (gestation <32 weeks) infants in resource-limited settings in sub-Saharan Africa (sSA) is critical to reducing high mortality and poor outcomes. Objective: To review evidence on feeding of VLBW/very preterm infants relevant to sSA. Methods: We searched the Cochrane Database of Systematic Reviews, Embase, PubMed and Cumulative Index to Nursing and Allied Health Literature (CINAHL) from inception to July 2019 to identify reviews of randomised and quasi-randomised controlled trials of feeding VLBW/very preterm infants. We focused on interventions that are readily available in sSA. Primary outcomes were weight gain during hospital stay and time to achieve full enteral feeds (120 mL/kg/day). Secondary outcomes were growth, common morbidities, mortality, duration of hospital stay and cognitive development. Quality of evidence (QOE) was assessed using the Measurement Tool to Assess Systematic Reviews (AMSTAR2). Results: Eight systematic reviews were included. Higher feed volume of day 1 (80 mL/kg) reduced late-onset sepsis and time to full enteral feeds, and higher feed volume (up to 300 mL/kg/day) improved weight gain without adverse events (QOE: low–moderate). Rapid advancement of feeds (30–40 mL/kg/day) was not associated with harm. Breast milk fortification with energy and protein increased growth and with prebiotics increased growth and reduced duration of admission (QOE: low–very low) and did not result in harm. Evidence regarding feeding tube placement and continuous versus bolus feeds was insufficient to draw conclusions. We found no reviews meeting our selection criteria regarding when to start feeds, use of preterm formula, cup-and-spoon feeding or gravity versus push feeds and none of the reviews included trials from low-income countries of sSA. Conclusions: The evidence base informing feeding of VLBW/very preterm babies in resource-limited settings in sSA is extremely limited. Pragmatic studies are needed to generate evidence to guide management and improve outcomes for these highly vulnerable infants. PROSPERO registration number: CRD42019140204.